Chronic recurrent Guillain-Barré syndrome: report of 3 cases - Antônio Rodrigues de Mello; Marcos R. G. de Freitas; Leila Chimelli (Arquivos de Neuro-Psiquiatria)
The classical Guillain-Barre syndrome is an acute or subacute polyradiculoneuropathy whose main clinical features are progressive weakness of the limbs, decrease or absence of tendon reflexes, and sensory changes. Although in most of the cases there is complete recovery in weeks or months, some patients have a slow and progressive relapsing course and present thickening of the peripheral nerves. In this paper we describe three cases of the chronic and relapsing variety of Guillain-Barré syndrome, two of which had prominent hypertrophic changes in the peripheral nerves with onion bulb formations The clinical and pathological features of this disease are reviewed. The three patients improved with the use of steroids.